Cherokee Stories of the Turtle Island Liars' Club - Teuton, Christopher B. (Book collections on Project MUSE., 2012)
Cherokee Stories of the Turtle Island Liars' Club paints a vivid, fascinating portrait of a community deeply grounded in tradition and dynamically engaged in the present. A collection of interwoven stories, conversations, and teachings about Western Cherokee life, beliefs, and the art of storytelling, the book orchestrates a multilayered conversation between a group of honored Cherokee elders, storytellers, and knowledge-keepers and the communities their stories touch. Collaborating with Hastings Shade, Sammy Still, Sequoyah Guess, and Woody Hansen, Cherokee scholar Christopher B. Teuton has a.